2019
DOI: 10.1097/md.0000000000018324
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of machine-learning-assisted detection for anterior cruciate ligament injury based on magnetic resonance imaging

Abstract: Background: Although many machine learning algorithms have been developed to detect anterior cruciate ligament (ACL) injury based on magnetic resonance imaging (MRI), the performance of different algorithms required further investigation. The objectives of this current systematic review are to evaluate the diagnostic accuracy of machine-learning-assisted detection for ACL injury based on MRI and find the current best algorithm. Method: We will conduct a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…More and more people are aware of its importance and related diseases, and their research is getting deeper and deeper. According to the analysis of 2725 cases of sports injuries in various sports events by the Institute of Sports Medicine, knee injuries accounted for 25.82%, accounting for the first of all sports injuries [ 1 ]. Different types and degrees of knee injuries have seriously affected athletes' training and sports performance.…”
Section: Introductionmentioning
confidence: 99%
“…More and more people are aware of its importance and related diseases, and their research is getting deeper and deeper. According to the analysis of 2725 cases of sports injuries in various sports events by the Institute of Sports Medicine, knee injuries accounted for 25.82%, accounting for the first of all sports injuries [ 1 ]. Different types and degrees of knee injuries have seriously affected athletes' training and sports performance.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of ACL tear was measured by the AUC for the injury-detection 0.894 problem and for full rupture case 0.943 after being coupled with both features and machine learning support vector machines (SVM) and random forest (RF). There are various surveys, meta-analyses and reviews [ 24 , 25 ] related to anterior cruciate ligament knee injury detection through various machine learning models. It has been shown that the accuracy remained good in the case of a smaller dataset, but in the case of more radiology images, the machine learning models have not been a solution.…”
Section: Related Workmentioning
confidence: 99%
“…Given the digital nature of data and the presence of structured data formats such as DICOM (Digital Imaging and Communications in Medicine), medical imaging has seen significant strides with the implementation of machine learning-based approaches to several imaging modalities, including Computed Tomography (CT), Magnetic Resonance Imaging (MRI), X-Ray, Positron Emission Tomography (PET), Ultrasound, and more. Several ML-based models have been developed to identify tumors [ 42 , 43 ], lesions [ 44 ], fractures [ 45 , 46 ], and tears [ 47 , 48 ].…”
Section: Ai In Healthcarementioning
confidence: 99%